2013
DOI: 10.1039/c3gc40899j
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of deep eutectic solvent–water binary mixtures for lipase-catalyzed lipophilization of phenolic acids

Abstract: This work reports the first lipase-catalyzed reactions between substrates of different polarities using deep eutectic solvents as a medium. The model reaction consisted of a lipophilization process based on the alcoholysis of phenolic esters using immobilized Candida antarctica lipase B as a biocatalyst. Results showed that water could dramatically improve the lipase activity and change the reactivity of phenolic substrates. Indeed, very low conversions (<2%) were observed in pure DES, whereas in DES–water bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
113
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 166 publications
(121 citation statements)
references
References 29 publications
6
113
0
2
Order By: Relevance
“…These properties have led to NADES replacing ionic liquids in many applications, as the usage of ionic liquids in foods and pharmaceuticals is generally avoided nowadays because of their potential toxicity [21, 22]. The field of applications of natural deep eutectic solvents is very broad, and includes for example the dissolution of DNA [11, 12], acting as media for enzyme reactions [23], biotransformations [24], biomass processing [25], the stabilization of pigments [16], and various extractions [26–29]. The pharmaceutical industry is another field in which NADES can be extremely useful; for instance, they can be used to improve the solubility of drugs that are poorly soluble in water [30, 31] and to enhance the bioactivities of dissolved species [32].…”
Section: Introductionmentioning
confidence: 99%
“…These properties have led to NADES replacing ionic liquids in many applications, as the usage of ionic liquids in foods and pharmaceuticals is generally avoided nowadays because of their potential toxicity [21, 22]. The field of applications of natural deep eutectic solvents is very broad, and includes for example the dissolution of DNA [11, 12], acting as media for enzyme reactions [23], biotransformations [24], biomass processing [25], the stabilization of pigments [16], and various extractions [26–29]. The pharmaceutical industry is another field in which NADES can be extremely useful; for instance, they can be used to improve the solubility of drugs that are poorly soluble in water [30, 31] and to enhance the bioactivities of dissolved species [32].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it has been demonstrated that DES based on choline chloride in a binary mixture with water could be effectively used for the alcoholysis of phenolic esters with 1-octanol, using immobilized C. antarctica lipase B as a biocatalyst. 64 In this study, we have shown that the lipase-catalyzed reactions of dissolved substrates in DES are extremely difficult to perform without the addition of water. The best results were obtained in DES based on choline chloride (ChCl) associated with urea (U) as a hydrogen-bond donor after adding water.…”
Section: Hélène Fulcrandmentioning
confidence: 99%
“…The DES forms hydrogenbonds with the surface residues of the enzyme which, instead of lipase denaturation, lead to greater enzyme stability. Numerous enzymes have been studied in such system and exhibited both high activity and unexpected promising stability: epoxide hydrolases [14,15], proteases such as subtilisin and a-chymotrypsin [16,17], esterases [15] and lipases [15,18,19]. Obviously, additional experiments are necessary to validate the statement in which NADES are involved in the biosynthesis pathways of the living organisms.…”
Section: From Eutectic To Deep Eutectic Solvents (Des)mentioning
confidence: 95%